Extraction of Titanium(IV) from its Hydrochloric Acid Solution with Indigenous Solvent, Tri-iso-Amyl Phosphate (TAP) - Hasan, S.H.; Joshi, V.C.; Rupainwar, D.C. (Asian Journal of Chemistry, 2010)
The indigenously prepared solvent tri-iso-amyl phosphate (TAP) obtained from fusel oil, a by-product of Indian Alcohol Industry, has been successfully utilised to extract titanium(IV) from its aqueous hydrochloric acid solutions. The effect of various parameters viz. [ATP], [H3O+], [Cl–], [Ti(IV)] on the extraction of the metal ion, has been investigated and discussed. The effect of using different diluents for TAP on the extraction reveals that the extraction is highest in the presence of non-polar diluents and this further substantiates the non-polar nature of the extracted species.